Another Look at the "Mercator Effect" on Global-Scale Cognitive Maps: Not in Areas but in Directions. Issue 2 (7th February 2022) - Montello, Daniel R.; Battersby, Sarah E.
Abstract : The Mercator effect is the widespread and persistent belief among cartographers and others that people's global-scale cognitive maps are distorted in a particular way because of their exposure to world maps displayed with the common Mercator projection. In particular, such exposure has been claimed to lead people to believe that polar regions, such as Greenland, are much larger than they really are, relative to equatorial regions. Recent studies, however, have found no evidence for a Mercator effect on recalled areas for world regions. Given that a version of the Mercator projection known as the Web Mercator has been used for Web mapping in the last couple of decades, we carried out a replication with samples at two universities, but we also asked respondents to estimate great-circle directions ("as a jet would fly") from their home city to several other world cities. We again find no support for a Mercator effect on areas estimated from memory, but our novel collection of spherical direction estimates provides clear evidence of a Mercator effect (or that of a similar rectangular projection) on directional beliefs. These results confirm that cognitive maps are not unitary, analogue mental structures but collections of beliefs stored in different formats in separate mental structures that are not necessarily mutually coordinated and integrated. We also introduce a survey of map use that focuses on digital maps and their use for local versus global geographic inquiries.